Systematic review of Kinect-based solutions for physical risk assessment in manual materials handling in industrial and laboratory environments. (December 2021) - Lunin, Alexander; Glock, Christoph H.
Highlights: Reviews the literature on Kinect-based solutions for ergonomic assessment. Develops a conceptual framework for classifying the literature. Discusses system setup and an ideal experimental structure for Kinect-based tools. Presents advantages and limitations of the current generation of Kinect-based tools. Supports the development auf (semi-)automatic systems for assessing ergonomic risks. Abstract: Due to demographic changes, the number of older workers employed in production and logistics environments increases continuously. During the execution of manual materials handling tasks that are still very common in these industries, especially older workers face an increased risk of developing musculoskeletal disorders (MSDs). The substantial MSD rates we can observe in many countries could be decreased through an improvement in working conditions. Ergonomic observational methods play an important role in this context: they facilitate an ergonomic risk assessment of workplaces and work processes and, by comparing system alternatives, help to lower MSD risks. Despite their advantages, these methods have also been criticized in the past, especially because they are time-consuming and often provide subjective results. Markerless motion capturing technology could be used to overcome some of the limitations of ergonomic observational methods, as they could quickly provide objective posture data of the worker. The aim of this paper is to provide a comprehensive review of works that develop solutions for evaluating manual materials handling activities at industrial workplaces using the Microsoft Kinect. Microsoft Kinect is an inexpensive markerless motion capturing system originally developed for Microsoft's Xbox gaming console that has recently been used in industry-type settings as well. Information collected in a systematic search of the literature is used to develop a conceptual framework that is then employed to discuss and synthesize the sampled literature. The results of this review support researchers and practitioners in developing and evaluating Kinect-based systems that support the ergonomic evaluation of workplaces and the consequent improvement of working conditions.